Seismic macrozonation of peninsular Malaysia and microzonation of Kuala Lumpur City Center and Putrajaya - Hendriyawan, Hendriyawan (2007)
This thesis presents seismic hazard assessment (SHA) which covers macrozonation analysis for Peninsular Malaysia and microzonation analysis focused on Kuala Lumpur City Centre (KLCC) and Putrajaya. The SHA is needed for mitigation of the effects of large earthquakes that may occur in the future. KLCC and Putrajaya are the two major areas selected because these are the main business centres and administration centres of Malaysia, respectively; hence they have significant numbers of settlements, high rise buildings, monumental structures and other critical facilities. Therefore, the risks of these areas are relatively higher than other cities in Peninsular Malaysia. Generally, there are four steps involved in conducting the macrozonation study: (1) collecting and analyzing earthquake data; (2) developing and characterizing seismic source models; (3) developing and selecting appropriate attenuation relationships; and (4) calculating seismic hazard using total probability theory. The results from this study are macrozonation maps for Peninsular Malaysia, uniform hazard spectra at bedrock and synthetic time histories for KLCC and Putrajaya. The probabilistic seismic hazard assessment (PSHA) is performed for 10% and 2% probability of exceedance (PE) in design time period of 50 years or the corresponding to return period of approximately 500 and 2,500 years, respectively. The results show that the peak ground acceleration (PGA) across Peninsular Malaysia are in the range of 20-100 gals and 40-200 gals for 10% and 2% PE in 50-year hazard levels, respectively. The hazard levels show that the trend of contour increasing consistently from the northeast to the southwest of Peninsular Malaysia. Microzonation study is performed in order to obtain ground motion parameters such as acceleration, amplification factor and response spectra at the surface of KLCC and Putrajaya. The analyses are carried out by using nonlinear one dimensional shear wave propagation analysis approach. The results of site response analysis at several points were used to develop contour of acceleration and amplification factors at the surface of KLCC and Putrajaya for 500 and 2,500-years return periods. The results show that the accelerations at the surface of KLCC are in the range of 80-220 gals and 170-340 gals for 500 and 2,500 years return periods, respectively. The amplification factors for those two hazard levels range between 1.2 and 2.9. The accelerations at the surface of Putrajaya are in the range of 130-190 gals and 220-340 gals for 500 and 2,500 years return periods, respectively. The amplification factors for those two hazard levels range between 1.6 and 2.6. Finally, the design response spectra for structural design purposes are proposed based on this research.